Effective virtual teams for new product development - Ale Ebrahim, N.; Ahmed, S.; Abdul Rashid, S.H.; Taha, Z. (Academic Journals, 2012)
At present, the existing literature shows that the factors which influence the effectiveness of virtual teams for new product development are still ambiguous. To address this problem, a research design was developed, which includes detailed literature review, preliminary model and field survey. From literature review, the factors which influence the effectiveness of virtual teams are identified and these factors are modified using a field survey. The relationship between knowledge workers (people), process and technology in virtual teams is explored in this study. The results of the study suggest that technology and process are tightly correlated and need to be considered early in virtual teams. The use of software as a service, web solution, report generator and tracking system should be incorporated for effectiveness virtual teams.